Micro-Anatomy of Small Intestine of Indigenous Piglets of Assam During Pre-Weaning Period - Rajkhowa, J.; Baishya, G. (Indian Journal of Veterinary Anatomy, 2013)
The present study was conducted on thirty indigenous pre-weaning piglets of Assam divided into five age groups. The epithelial lining of small intestine was simple columnar with numerous goblet cells. The villi of duodenum were long and slender which decreased towards the ileum. The lamina propria mucosae was composed of areolar connective tissue with blood vessels, nerves, lacteals and intestinal glands. Numerous diffuse and aggregated lymphoid tissue was observed throughout the intestine. The lamina muscularis mucosae was comprised of two layers of smooth muscle fibres. Tunica submucosa was consisted of loose connective tissue and tubulo-alveolar Brunner’s glands in duodenum. The size of the follicles and intrafollicular areas of Peyer’s patches increased with the advancement of age of the piglets.